Self-organized TiO2 nanotube arrays sensitized by uniform Cd0.8Zn0.2S nanoparticles for highly effective photoelectrochemical performance. (15th February 2016) - Wang, Q.Y.; Xu, Y.B.; Zhang, S.H.; Gao, S.M.; Zheng, Q.D.; Yuan, Q.Q.; Rong, W.Q.; Yin, C.L.; Wang, J.F.; Wang, M.J.
Abstract: TiO2 nanotube arrays sensitized by Cd0.8 Zn0.2 S nanoparticles (TiO2 NTs/CZS) were successfully fabricated by a two-step process of anodization followed by a hydrothermal method. Phase compositions and morphologies of TiO2 NTs/CZS were characterized by XRD and SEM, and the sensitization significantly improved the visible light response of TiO2 NTs, covering the UV and visible light with wavelengths below 550 nm. TiO2 NTs/CZS showed high visible light photocurrent densities, which was attributed to the high visible light harvesting and the effective charge carrier separation derived from the coupling effect of TiO2 NTs and CZS. TiO2 NTs/CZS also showed high photoelectrocatalytic properties, including decomposition of methyl orange (MO) and reduction of Cr(VI) into Cr(III). Graphical abstract: Highlights: TiO2 NTs sensitized by Cd0.8 Zn0.2 S nanoparticles were prepared by a hydrothermal method. Cd0.8 Zn0.2 S sensitization significantly enhances the visible light response of TiO2 NTs. TiO2 NTs/Cd0.8 Zn0.2 S exhibit excellent photocurrent and photoelectrocatalytic removal of MO and Cr(VI).